2000
DOI: 10.1034/j.1600-0773.2000.pto870209.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro and in vivo Developmental Toxicity and Pharmacokinetics of Phenytoin in the Rat

Abstract: Abstract:The rat whole embryo culture was compared to an in vivo experiment with regard to embryotoxicity as well as exposure characteristics, using phenytoin as a model compound. Intra-embryonic concentrations and their embryotoxic effects were determined on gestation day 11 after in vitro administration of 50-150 mg/ml or in vivo gavage of 500-1500 mg/kg body-weight on gestation day 10. In addition, exposure kinetics were studied in vivo after a single oral dose on gestation day 10, and developmental defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The results of our study clearly show that oral administration of DPH is minimally embryotoxic at a minimal maternotoxic dose and significantly embryotoxic and teratogenic at an overt maternotoxic dose. Similar developmental toxicities have been demonstrated in a range of animal species including the rat (Rowland et al ; Finnell and Dansky ; Beekhuijzen et al, ). However, some human studies have cast doubt on the association between DPH exposure and teratologic risk (Livingston et al, ; Meyer, ; Goujard et al, ; Shepard and Lemire, ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of our study clearly show that oral administration of DPH is minimally embryotoxic at a minimal maternotoxic dose and significantly embryotoxic and teratogenic at an overt maternotoxic dose. Similar developmental toxicities have been demonstrated in a range of animal species including the rat (Rowland et al ; Finnell and Dansky ; Beekhuijzen et al, ). However, some human studies have cast doubt on the association between DPH exposure and teratologic risk (Livingston et al, ; Meyer, ; Goujard et al, ; Shepard and Lemire, ).…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, the significant embryotoxicity and teratogenicity observed in the 300 mg/kg group was considered to be a direct effect of DPH. According to a report by Beekhuijzen et al (), developmental toxicity of DPH is specific and not mediated by maternal toxicity. In vitro experimental studies have also shown that treating rodent embryos with DPH directly causes malformations encompassing allantois circulation, crown‐rump length, somite number, and yolk sac diameter (Beekhuijzen et al, ; Abramov and Wells, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is worthy to point out there are reports that CPA‐induced neurotoxicity was potented by activate excitotoxic mechanisms in vitro and in vivo (Rzeski et al, 2004; Jansen et al, 2006). Although evidence of CPA‐induced retardation in neurogrowth exists (Mammon et al, 2006; Beekhuijzen et al, 2000), further studies are needed to elucidate the mechanisms for CPA‐induced impairments process leading to malformation before and after neural tube closure.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic analysis revealed comparable intra-embryonic concentrations at this time point, but the comparison of the concentrationtime curves revealed that the AUC values for the in vivo embryos were much lower than the AUC values obtained in vitro. A subsequent in vitro experiment with lower AUC values comparable to the maximal AUC values obtained in vivo thus revealed no adverse effects in the cultured embryo [103]. A very similar study performed with hydroxyurea and the same focus had the same outcome [104].…”
Section: Pharmacokinetic Aspects In Wecmentioning
confidence: 74%
“…It is reasonable to suggest that known pharmacokinetic drug parameters like peak concentration and half-life in vivo have to be mimicked in vitro in order to obtain a comparability of results [95]. For example, in a comparative study on the embryotoxicity of phenytoin [103], it was observed that the embryos exposed in vivo showed no significant effect on embryonic development on gestational day 11, whereas the embryos exposed in vitro did. Pharmacokinetic analysis revealed comparable intra-embryonic concentrations at this time point, but the comparison of the concentrationtime curves revealed that the AUC values for the in vivo embryos were much lower than the AUC values obtained in vitro.…”
Section: Pharmacokinetic Aspects In Wecmentioning
confidence: 99%